Burnout dan Niat untuk Keluar dari Pekerjaan : Perceived Organizational Support sebagai Variabel Moderasi - Indriani, Riri; Novriadi, Asep; Zaitul, Zaitul (Innovative: Journal Of Social Science Research, 2025)
Burnout in health workers often leads to high turnover intention, which can disrupt the stability of hospital services. With adequate organisational support, perceived organizational support (POS) is considered to have the capacity to act as a mediator. The purpose of this study was to determine the relationship between burnout and turnover intention at Aisyiah Hospital, Pariaman City and the role of POS as a moderator variable in health workers. This study employed a quantitative approach, collecting primary data through a survey using a 1-5 Likert scale. The research sample was 40 health workers selected as respondents. Data analysis employed SmartPLS with the Multivariate Analysis (MMA) method and Structural Equation Modelling (SEM) based on Partial Least Squares (PLS). The results showed that stress had a significant effect on turnover intention. In addition, the study showed that POS moderated the relationship between stress and turnover intention, meaning that organisational support affected burnout and the willingness of health workers to leave their jobs. These results suggest that increasing POS can be a useful approach to reducing the desire to leave work due to fatigue. Therefore, to retain qualified health workers, hospital management must strengthen organisational support, including recognition, attention to employee welfare, and pro-employee policies.